KESALAHAN PENULISAN KOP SURAT DINAS INSTANSI PEMERINTAH DI KOTA BANJARMASIN - Ahmad Zaini (Balai Bahasa Kalimatan Selatan, 2019)
Official letter is a means of communication in an institution. However, there are still many official letterheads written in incorrectly writing conventions. The objective of this research is to study the level of error writing in official letterheads of government institution in the city of Banjarmasin. The approach of this reaearch is a quantitative and qualitative approach with descriptive methods. Data and data sources were obtained from official letters issued by relevant institutions by using documentation techniques. The data were processed in Microsoft Exel, then they were displayed in graph and after that the data were analyzed. The results of this study show that the most error writing in official letterhead of government institutions in the Banjarmasin city were 44% in word writing, 20% in the use of punctuation, 17% in the use of abbreviation / acronym, and 14% in the usage.